Engender student-teachers’ english communication skills in a public university in Sabah - Tan, Choon Keong; Kang, Hwa Choo (Opción, 2019)
This research explores the use of Padlet.com to promote student teachers’ communicative skills through collaborative knowledge building. Questionnaire and focus-group interviews were used to gather data as a method. It was found that Padlet.com has successfully improved student teachers’ English communicative skills through collaborative knowledge building in particularly learners’ preparedness (mean=3.91), academic improvement (mean=3.46), flexible learning (mean=3.78) and learning management (mean=3.89). In conclusion, it is recommended that Padlet.com be used as a future online learning tool for improving learning in the university.